(untitled) (CIPEEX, 2025)
Introduction: Pediatric asthma is challenging to control due to its varied inflammatory nature among patients. Biological therapies, such as monoclonal antibodies (MABs), have emerged as an innovative approach, but treatment response can vary, highlighting the need for more personalized approaches. However, selecting and monitoring these therapies still face considerable challenges. Objective: This study aims to review the effectiveness, safety, and challenges associated with the use of MABs approved for children and adolescents with severe asthma. Methodology: An integrative review was conducted based on the PICO model (population, intervention, comparison, and outcome). The focus was on pediatric patients with chronic asthma (P), evaluating the use of MABs (I) compared to non-MAB treatments, different MABs, or no treatment (C), aiming for significant symptom improvement in asthma (O). Results and Discussion: Among the MABs used to treat severe asthma, five are approved for use in children and adolescents: omalizumab, mepolizumab, benralizumab, dupilumab, and tezepelumab, all representing a significant shift in managing severe pediatric asthma. Omalizumab, by binding to immunoglobulin E (IgE), was the first to be widely accepted as safe and effective, significantly reducing asthma exacerbations with a low risk of anaphylaxis. Mepolizumab and benralizumab, which block interleukin-5 (IL-5), have also shown efficacy in reducing exacerbations and improving symptoms. Additionally, dupilumab, which blocks the alpha receptor of interleukin-4 (IL-4Rα), and tezepelumab, which inhibits the thymic stromal lymphopoietin protein (TSLP), are effective in reducing exacerbations, improving lung function, and controlling symptoms in patients with different severe asthma phenotypes. Although dupilumab and tezepelumab are the newest in the class and require further studies, especially regarding tolerability, tezepelumab stands out for its approval without phenotype restriction, broadening treatment options. The choice of the most appropriate MAB should consider factors such as the patient’s age, asthma phenotype, disease severity, and comorbidities. Although generally safe and well-tolerated, biologics reduce the need for systemic corticosteroids and present rare events of anaphylaxis related to hypersensitivity reactions. However, challenges persist, such as limited access, high costs, and a lack of long-term studies, particularly in younger children. More research is needed to assess the safety and efficacy of MABs in children and adolescents. Conclusion: MABs represent a significant advancement in the treatment of severe pediatric asthma, offering more personalized therapeutic options. All these medications have the potential to improve quality of life, reduce exacerbations, and enhance asthma control. Additionally, they contribute to improving lung function and reducing the use of harmful palliative medications such as oral corticosteroids. However, it is crucial to improve the processes of selection, monitoring, and access to these medications, ensuring individualized treatments. Ongoing research is essential to optimize the management of this complex condition and further explore the potential of this drug class.